Regulate or tolerate: Thermal strategy of a coral reef flat resident, the epaulette shark, Hemiscyllium ocellatum. Issue 3 (12th December 2020) - Nay, Tiffany J; Longbottom, Rohan J; Gervais, Connor R; Johansen, Jacob L; Steffensen, John F; Rummer, Jodie L; Hoey, Andrew S
ABSTRACT: Highly variable thermal environments, such as coral reef flats, are challenging for marine ectotherms and are thought to invoke the use of behavioural strategies to avoid extreme temperatures and seek out thermal environments close to their preferred temperatures. Common to coral reef flats, the epaulette shark ( Hemiscyllium ocellatum ) possesses physiological adaptations to hypoxic and hypercapnic conditions, such as those experienced on reef flats, but little is known regarding the thermal strategies used by these sharks. We investigated whether H. ocellatum uses behavioural thermoregulation ( i.e ., movement to occupy thermally favourable microhabitats) or tolerates the broad range of temperatures experienced on the reef flat. Using an automated shuttlebox system, we determined the preferred temperature of H. ocellatum under controlled laboratory conditions and then compared this preferred temperature to 6 months of in situ environmental and body temperatures of individual H. ocellatum across the Heron Island reef flat. The preferred temperature of H. ocellatum under controlled conditions was 20.7 ± 1.5°C, but the body temperatures of individual H. ocellatum on the Heron Island reef flat mirrored environmental temperatures regardless of season or month. Despite substantial temporal variation in temperature on the Heron Island reef flat (15–34°C during 2017), there was a lack of spatial variation in temperature across the reef flat between sites or microhabitats. This limited spatial variation in temperature creates a low‐quality thermal habitat limiting the ability of H. ocellatum to behaviourally thermoregulate. Behavioural thermoregulation is assumed in many shark species, but it appears that H. ocellatum may utilize other physiological strategies to cope with extreme temperature fluctuations on coral reef flats. While H. ocellatum appears to be able to tolerate acute exposure to temperatures well outside of their preferred temperature, it is unclear how this, and other, species will cope as temperatures continue to rise and approach their critical thermal limits. Understanding how species will respond to continued warming and the strategies they may use will be key to predicting future populations and assemblages.